(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
The problem-integrative study of chemistry is the simultaneous acquisition of knowledge and skills by students, the integration and synthesis of this knowledge in the process of identifying, forming and concluding related interdisciplinary educational problems. , the development aimed at their use is considered a holistic methodological system of research. Problem stories and learning difficulties in integrative-interdisciplinary teaching create a basis for engaging students in functional cognitive work.